La Oralidad en el Proceso Civil: ¿Es factible el dictado de una Sentencia Oral? Respuesta acorde a las garantías procesales argentinas y españolas - Groppo, Patricio Gustavo (2024)
For centuries there has been debate as to which system is better for settling civil disputes. Thus, while some postulate that the written system is better because it provides greater legal certainty, others are inclined towards the oral system because of the undeniable reduction of procedural time and the benefits of the immediacy between the judge and the parties. Within this dichotomy, this paper seeks to analyze the advantages and disadvantages of oral sentencing in Spain, where it is expressly prohibited, and in Argentina, where there is no specific prohibition in the legal system. Before doing so, a retrospective view of the history of orality in both countries will be made.